Preparation method of silver nanomaterial-loaded flexible carbon fiber sensor and application of sensor in sweat detection

By using silver nanomaterial-loaded flexible carbon fiber preparation method in sweat sensors, the stability and efficiency problems of enzyme-sensitive elements are solved, and a sweat sensor with high hydrophilicity and high detection efficiency is achieved, with chemical stability and flexibility.

CN119881045APending Publication Date: 2025-04-25JILIN INST OF PHYSICAL EDUCATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510056181.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

When using enzymes as sensitive components, there are problems such as poor stability, limited one-time use, low sampling efficiency, complex calibration requirements, and affected by sweat turbidity.

Method used

Using the preparation method of silver nanomaterial loaded flexible carbon fiber sensor, sensors with high hydrophilicity and high detection efficiency are prepared through electrochemical oxidation treatment and electrodeposition technology.

Benefits of technology

The sensor is chemical stability, flexibility, lightness, durability and cycle stability, and can actively absorb sweat, realize real-time monitoring, and improve detection efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119881045A_ABST
    Figure CN119881045A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a silver nanomaterial-loaded flexible carbon fiber sensor and application of the sensor in sweat detection, and relates to the technical field of micro-nano sensing and flexible electronics. The invention aims to solve the problems of poor stability, disposable use limitation, low sampling efficiency, complex calibration requirements and influence of sweat turbidity when a sweat sensor adopts enzyme as a sensitive element. The method comprises the following steps: 1, pretreating carbon fibers; 2, preparing a surface-functionalized carbon fiber material; 3, preparing a silver nano material loaded flexible carbon fiber; and 4, compounding. According to the method, a large number of oxygen-containing functional groups such as hydroxyl and carboxyl are introduced to the surface of the carbon fiber material through electrochemical oxidation treatment, the surface activity of the carbon fiber material is increased through the functional groups, and therefore the hydrophilicity of the carbon fiber material is improved. Due to improvement of hydrophilicity, the carbon fiber material can actively absorb sweat, so that a real-time monitoring effect is achieved, and the carbon fiber material has chemical stability, flexibility, light weight, durability and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of micro-nano sensing and flexible electronic technology, and in particular to a method for preparing a silver nanomaterial-loaded flexible carbon fiber sensor and an application thereof in sweat detection. Background Art

[0002] As society pays more attention to health and disease prevention, wearable sensors have received widespread attention in the field of health monitoring because they can monitor human physiological parameters such as heart rate and blood oxygen saturation in real time. Wearable sensors are not only widely used in the field of health monitoring, but also show broad application prospects in disease diagnosis, rehabilitation treatment and daily health assessment. Despite the rapid development of wearable sensors, they still face challenges such as improving sensitivity, stability, comfort and biocompatibility. Future development directions include improving the flexibility of materials, developing new sensors and integrating more functions.

[0003] Sweat is a biofluid that is easily accessible and rich in biomarkers (such as salt ions, lactate, glucose, and cortisol). The metabolism of these substances is closely related to human health, so sweat can be used as an ideal object for human health monitoring. Wearable sweat sensors may become an alternative to traditional chemical analysis due to their advantages such as portability, non-invasiveness, comfort, and continuous monitoring. They can fit closely to human skin and have strong flexibility, comfort, and portability, bringing unlimited possibilities to the fields of health monitoring, disease diagnosis, and medical care.

[0004] Currently, when sweat sensors use enzymes as sensitive elements, the main disadvantages include poor stability, one-time use limitations, low sampling efficiency, complex calibration requirements, and being affected by sweat turbidity. Summary of the invention

[0005] The purpose of the present invention is to solve the problems of poor stability, one-time use limitation, low sampling efficiency, complex calibration requirements and influence of sweat turbidity when sweat sensors use enzymes as sensitive elements, and to provide a method for preparing a silver nanomaterial-loaded flexible carbon fiber sensor and its application in sweat detection.

[0006] A method for preparing a silver nanomaterial-loaded flexible carbon fiber sensor is specifically completed by the following steps:

[0007] 1. Pretreatment of carbon fiber:

[0008] Firstly, the carbon fiber material is cut, then ultrasonically cleaned, and then dried to obtain a pretreated carbon fiber material;

[0009] 2. In a three-electrode electrolytic cell, the pretreated carbon fiber material is used as the working electrode, the platinum sheet is used as the counter electrode, the Ag / AgCl electrode is used as the reference electrode, and the neutral salt solution is used as the electrolyte. Under the potential window of 0-1 V, the cyclic voltammetry scan rate is selected to perform electrochemical oxidation for a certain number of cycles at room temperature, and then the working electrode is taken out for washing and vacuum drying to obtain a surface functionalized carbon fiber material;

[0010] 3. At room temperature, the surface functionalized carbon fiber material was immersed in a mixed solution of AgNO3 and NaNO3, and a three-electrode system was used, with the surface functionalized carbon fiber material as the working electrode, the platinum sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode. The electrodeposition was performed for a period of time at an applied voltage of -0.3 V to obtain a silver nanomaterial-loaded flexible carbon fiber;

[0011] Fourth, compound the isolation layer and the silver nanomaterial-loaded flexible carbon fiber together to obtain a silver nanomaterial-loaded flexible carbon fiber sensor.

[0012] Principle of the present invention:

[0013] Electrochemical oxidation treatment will introduce a large number of oxygen-containing functional groups such as hydroxyl and carboxyl groups on the surface of carbon fiber materials. These functional groups increase the surface activity of carbon fiber materials, thereby improving the hydrophilicity of carbon fiber materials. The increase in hydrophilicity enables carbon fiber materials to actively absorb sweat, thereby achieving the effect of real-time monitoring. After actively absorbing sweat, the carbon fiber material penetrates into the isolation layer (polyvinyl alcohol) to interconnect the silver nanomaterial-loaded flexible carbon fiber and the isolation layer, and detect biological substances and inorganic salts in sweat, thereby improving the detection efficiency of the sensor device.

[0014] Advantages of the present invention:

[0015] 1. The silver nanomaterial-loaded flexible carbon fiber sensor prepared by the present invention has chemical stability, flexibility, lightness, durability and cycle stability;

[0016] Second, the present invention utilizes electrodes modified by precious metals and carbon fiber materials and adopts structural process design to overcome the shortcomings of using enzymes as sensitive elements.

[0017] 3. The sensor of the present invention can actively absorb sweat and realize real-time monitoring, and has a high detection efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a SEM image of the silver nanomaterial-loaded flexible carbon fiber prepared in Example 3 of the present invention;

[0019] Figure 2This is a test graph of voltage responses of sodium chloride solutions of different concentrations measured by the silver nanomaterial-loaded flexible carbon fiber sensor prepared in Example 3 of the present invention;

[0020] Figure 3 The figure is a relationship diagram between the fitted sodium chloride solutions of different concentrations and the response voltages of sodium chloride solutions of different concentrations measured by the silver nanomaterial-loaded flexible carbon fiber sensor prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0021] Specific implementation method 1: This implementation method is a method for preparing a silver nanomaterial-loaded flexible carbon fiber sensor, which is specifically completed by the following steps:

[0022] 1. Pretreatment of carbon fiber:

[0023] Firstly, the carbon fiber material is cut, then ultrasonically cleaned, and then dried to obtain a pretreated carbon fiber material;

[0024] 2. In a three-electrode electrolytic cell, the pretreated carbon fiber material is used as the working electrode, the platinum sheet is used as the counter electrode, the Ag / AgCl electrode is used as the reference electrode, and the neutral salt solution is used as the electrolyte. Under the potential window of 0-1 V, the cyclic voltammetry scan rate is selected to perform electrochemical oxidation for a certain number of cycles at room temperature, and then the working electrode is taken out for washing and vacuum drying to obtain a surface functionalized carbon fiber material;

[0025] 3. At room temperature, the surface functionalized carbon fiber material was immersed in a mixed solution of AgNO3 and NaNO3, and a three-electrode system was used, with the surface functionalized carbon fiber material as the working electrode, the platinum sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode. The electrodeposition was performed for a period of time at an applied voltage of -0.3 V to obtain a silver nanomaterial-loaded flexible carbon fiber;

[0026] Fourth, compound the isolation layer and the silver nanomaterial-loaded flexible carbon fiber together to obtain a silver nanomaterial-loaded flexible carbon fiber sensor.

[0027] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the carbon fiber material described in step 1 is carbon fiber cloth, carbon fiber felt, carbon fiber sponge or carbon fiber prepreg; in step 1, the carbon fiber material is cut into small pieces with a size of (1cm to 3cm)×(1cm to 3cm). The other steps are the same as those in specific implementation method 1.

[0028] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that: the ultrasonic cleaning process described in step 1 is: ultrasonic cleaning is performed using acetone, anhydrous ethanol and deionized water in sequence for 10 min to 60 min respectively; the drying temperature described in step 1 is 60° C. to 90° C. The other steps are the same as those of specific embodiment 1 or 2.

[0029] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the neutral salt solution described in step 2 is a sodium sulfate solution, a potassium sulfate solution, a zinc sulfate solution or a ferric sulfate solution. The other steps are the same as those of specific embodiments 1 to 3.

[0030] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the concentration of the neutral salt solution in step 2 is 1 mol / L to 3 mol / L. The other steps are the same as those of specific embodiments 1 to 4.

[0031] Specific embodiment 6: The difference between this embodiment and specific embodiments 1 to 5 is that the number of electrochemical oxidation cycles in step 2 is 10 to 30 cycles; the cyclic voltammetry scan rate in step 2 is 1 mVs -1 ~10mVs -1 The other steps are the same as those in Specific Embodiments 1 to 5.

[0032] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: in step 2, the working electrode is taken out and washed with deionized water for 3 to 5 times; the vacuum drying temperature in step 2 is 60°C; the electrodeposition time in step 3 is 10s to 90s. The other steps are the same as those in specific embodiments 1 to 6.

[0033] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that the mixed solution of AgNO3 and NaNO3 described in step three is obtained by dissolving AgNO3 and NaNO3 in water, wherein the concentration of AgNO3 is 10mmol / L to 50mmol / L, and the concentration of NaNO3 is 1mol / L to 10mol / L. The other steps are the same as those of specific embodiments one to seven.

[0034] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the material of the isolation layer described in step 4 is polyvinyl alcohol; the method of compounding the isolation layer with the silver nanomaterial-loaded flexible carbon fiber in step 4 is: using medical tape to adhere the isolation layer with the silver nanomaterial-loaded flexible carbon fiber or sew the isolation layer with the silver nanomaterial-loaded flexible carbon fiber together. The other steps are the same as specific embodiments 1 to 8.

[0035] Specific implementation method ten: This implementation method is a silver nanomaterial-loaded flexible carbon fiber sensor for sweat detection.

[0036] The following examples are used to verify the beneficial effects of the present invention:

[0037] Example 1: A method for preparing a silver nanomaterial-loaded flexible carbon fiber sensor is specifically completed by the following steps:

[0038] 1. Pretreatment of carbon fiber:

[0039] The carbon fiber cloth was cut into small pieces of 1 cm×1 cm in size, and then ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 10 min respectively, and dried at 60°C for 12 h to obtain the pretreated carbon fiber material;

[0040] 2. In a three-electrode electrolytic cell, the pretreated carbon fiber material is used as the working electrode, the platinum sheet is used as the counter electrode, the Ag / AgCl electrode is used as the reference electrode, and the neutral salt solution is used as the electrolyte. Under the potential window of 0-1 V, the cyclic voltammetry scan rate is selected to perform electrochemical oxidation for a certain number of cycles at room temperature, and then the working electrode is taken out for washing and vacuum drying to obtain a surface functionalized carbon fiber material;

[0041] The neutral salt solution described in step 2 is a sodium sulfate solution with a concentration of 1 mol / L;

[0042] The number of cycles of electrochemical oxidation described in step 2 is 10 cycles;

[0043] The cyclic voltammetry scan rate in step 2 was 1 mVs -1 ;

[0044] In step 2, the working electrode is taken out and washed three times with deionized water;

[0045] The vacuum drying temperature in step 2 is 60°C;

[0046] 3. At room temperature, the surface functionalized carbon fiber material was immersed in a mixed solution of AgNO3 and NaNO3, and a three-electrode system was used, with the surface functionalized carbon fiber material as the working electrode, the platinum sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode. The electrodeposition was performed for a period of time at an applied voltage of -0.3 V to obtain a silver nanomaterial-loaded flexible carbon fiber;

[0047] The electrodeposition time described in step 3 is 10 s;

[0048] The mixed solution of AgNO3 and NaNO3 described in step 3 is obtained by dissolving AgNO3 and NaNO3 in water, wherein the concentration of AgNO3 is 20mmol / L and the concentration of NaNO3 is 1mol / L;

[0049] Fourth, compounding the isolation layer with the silver nanomaterial-loaded flexible carbon fiber to obtain a silver nanomaterial-loaded flexible carbon fiber sensor;

[0050] The material of the isolation layer described in step 4 is polyvinyl alcohol;

[0051] The method for compounding the isolation layer and the silver nanomaterial-loaded flexible carbon fiber in step 4 is: using medical tape to adhere the isolation layer and the silver nanomaterial-loaded flexible carbon fiber together.

[0052] Example 2: A method for preparing a silver nanomaterial-loaded flexible carbon fiber sensor is specifically completed by the following steps:

[0053] 1. Pretreatment of carbon fiber:

[0054] The carbon fiber cloth was cut into small pieces of 1 cm×2 cm in size, and then ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 40 min respectively, and dried at 70°C for 12 h to obtain the pretreated carbon fiber material;

[0055] 2. In a three-electrode electrolytic cell, the pretreated carbon fiber material is used as the working electrode, the platinum sheet is used as the counter electrode, the Ag / AgCl electrode is used as the reference electrode, and the neutral salt solution is used as the electrolyte. Under the potential window of 0-1 V, the cyclic voltammetry scan rate is selected to perform electrochemical oxidation for a certain number of cycles at room temperature, and then the working electrode is taken out for washing and vacuum drying to obtain a surface functionalized carbon fiber material;

[0056] The neutral salt solution described in step 2 is a sodium sulfate solution with a concentration of 2 mol / L;

[0057] The number of electrochemical oxidation cycles described in step 2 is 15 cycles;

[0058] The cyclic voltammetry scan rate in step 2 was 2 mVs -1 ;

[0059] In step 2, the working electrode is taken out and washed three times with deionized water;

[0060] The vacuum drying temperature in step 2 is 60°C;

[0061] 3. At room temperature, the surface functionalized carbon fiber material was immersed in a mixed solution of AgNO3 and NaNO3, and a three-electrode system was used, with the surface functionalized carbon fiber material as the working electrode, the platinum sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode. The electrodeposition was performed for a period of time at an applied voltage of -0.3 V to obtain a silver nanomaterial-loaded flexible carbon fiber;

[0062] The electrodeposition time described in step 3 is 20 s;

[0063] The mixed solution of AgNO3 and NaNO3 described in step 3 is obtained by dissolving AgNO3 and NaNO3 in water, wherein the concentration of AgNO3 is 40mmol / L and the concentration of NaNO3 is 2mol / L;

[0064] Fourth, compounding the isolation layer with the silver nanomaterial-loaded flexible carbon fiber to obtain a silver nanomaterial-loaded flexible carbon fiber sensor;

[0065] The material of the isolation layer described in step 4 is polyvinyl alcohol;

[0066] The method for compounding the isolation layer and the silver nanomaterial-loaded flexible carbon fiber in step 4 is: using medical tape to adhere the isolation layer and the silver nanomaterial-loaded flexible carbon fiber together.

[0067] Example 3: A method for preparing a silver nanomaterial-loaded flexible carbon fiber sensor is specifically completed by the following steps:

[0068] 1. Pretreatment of carbon fiber:

[0069] The carbon fiber cloth was cut into small pieces of 2 cm × 2 cm in size, and then ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 40 min respectively, and dried at 60 ° C for 12 h to obtain the pretreated carbon fiber material;

[0070] 2. In a three-electrode electrolytic cell, the pretreated carbon fiber material is used as the working electrode, the platinum sheet is used as the counter electrode, the Ag / AgCl electrode is used as the reference electrode, and the neutral salt solution is used as the electrolyte. Under the potential window of 0-1 V, the cyclic voltammetry scan rate is selected to perform electrochemical oxidation for a certain number of cycles at room temperature, and then the working electrode is taken out for washing and vacuum drying to obtain a surface functionalized carbon fiber material;

[0071] The neutral salt solution described in step 2 is a sodium sulfate solution with a concentration of 1 mol / L;

[0072] The number of electrochemical oxidation cycles described in step 2 is 20 cycles;

[0073] The cyclic voltammetry scan rate in step 2 was 3 mVs -1 ;

[0074] In step 2, the working electrode is taken out and washed three times with deionized water;

[0075] The vacuum drying temperature in step 2 is 60°C;

[0076] 3. At room temperature, the surface functionalized carbon fiber material was immersed in a mixed solution of AgNO3 and NaNO3, and a three-electrode system was used, with the surface functionalized carbon fiber material as the working electrode, the platinum sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode. The electrodeposition was performed for a period of time at an applied voltage of -0.3 V to obtain a silver nanomaterial-loaded flexible carbon fiber;

[0077] The electrodeposition time described in step 3 is 20 s;

[0078] The mixed solution of AgNO3 and NaNO3 described in step 3 is obtained by dissolving AgNO3 and NaNO3 in water, wherein the concentration of AgNO3 is 60mmol / L and the concentration of NaNO3 is 3mol / L;

[0079] Fourth, compounding the isolation layer with the silver nanomaterial-loaded flexible carbon fiber to obtain a silver nanomaterial-loaded flexible carbon fiber sensor;

[0080] The material of the isolation layer described in step 4 is polyvinyl alcohol;

[0081] The method for compounding the isolation layer and the silver nanomaterial-loaded flexible carbon fiber in step 4 is: using medical tape to adhere the isolation layer and the silver nanomaterial-loaded flexible carbon fiber together.

[0082] Example 4: A method for preparing a silver nanomaterial-loaded flexible carbon fiber sensor is specifically completed by the following steps:

[0083] 1. Pretreatment of carbon fiber:

[0084] The carbon fiber cloth was cut into small pieces of 3 cm × 3 cm in size, and then ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 6 min respectively, and dried at 90 ° C for 12 h to obtain the pretreated carbon fiber material;

[0085] 2. In a three-electrode electrolytic cell, the pretreated carbon fiber material is used as the working electrode, the platinum sheet is used as the counter electrode, the Ag / AgCl electrode is used as the reference electrode, and the neutral salt solution is used as the electrolyte. Under the potential window of 0-1 V, the cyclic voltammetry scan rate is selected to perform electrochemical oxidation for a certain number of cycles at room temperature, and then the working electrode is taken out for washing and vacuum drying to obtain a surface functionalized carbon fiber material;

[0086] The neutral salt solution described in step 2 is a sodium sulfate solution with a concentration of 3 mol / L;

[0087] The number of electrochemical oxidation cycles described in step 2 is 30 cycles;

[0088] The cyclic voltammetry scan rate in step 2 was 4 mVs -1 ;

[0089] In step 2, the working electrode is taken out and washed three times with deionized water;

[0090] The vacuum drying temperature in step 2 is 60°C;

[0091] 3. At room temperature, the surface functionalized carbon fiber material was immersed in a mixed solution of AgNO3 and NaNO3, and a three-electrode system was used, with the surface functionalized carbon fiber material as the working electrode, the platinum sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode. The electrodeposition was performed for a period of time at an applied voltage of -0.3 V to obtain a silver nanomaterial-loaded flexible carbon fiber;

[0092] The electrodeposition time described in step 3 is 20 s;

[0093] The mixed solution of AgNO3 and NaNO3 described in step 3 is obtained by dissolving AgNO3 and NaNO3 in water, wherein the concentration of AgNO3 is 80mmol / L and the concentration of NaNO3 is 4mol / L;

[0094] Fourth, compounding the isolation layer with the silver nanomaterial-loaded flexible carbon fiber to obtain a silver nanomaterial-loaded flexible carbon fiber sensor;

[0095] The material of the isolation layer described in step 4 is polyvinyl alcohol;

[0096] The method for compounding the isolation layer and the silver nanomaterial-loaded flexible carbon fiber in step 4 is: using medical tape to adhere the isolation layer and the silver nanomaterial-loaded flexible carbon fiber together.

[0097] Example 5: A method for preparing a silver nanomaterial-loaded flexible carbon fiber sensor is specifically completed by the following steps:

[0098] 1. Pretreatment of carbon fiber:

[0099] The carbon fiber cloth was cut into small pieces of 2 cm × 3 cm in size, and then ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 50 min respectively, and then dried at 80 ° C for 12 h to obtain the pretreated carbon fiber material;

[0100] 2. In a three-electrode electrolytic cell, the pretreated carbon fiber material is used as the working electrode, the platinum sheet is used as the counter electrode, the Ag / AgCl electrode is used as the reference electrode, and the neutral salt solution is used as the electrolyte. Under the potential window of 0-1 V, the cyclic voltammetry scan rate is selected to perform electrochemical oxidation for a certain number of cycles at room temperature, and then the working electrode is taken out for washing and vacuum drying to obtain a surface functionalized carbon fiber material;

[0101] The neutral salt solution described in step 2 is a sodium sulfate solution with a concentration of 2 mol / L;

[0102] The number of cycles of electrochemical oxidation described in step 2 is 20 cycles;

[0103] The cyclic voltammetry scan rate in step 2 was 4 mVs -1 ;

[0104] In step 2, the working electrode is taken out and washed three times with deionized water;

[0105] The vacuum drying temperature in step 2 is 60°C;

[0106] 3. At room temperature, the surface functionalized carbon fiber material was immersed in a mixed solution of AgNO3 and NaNO3, and a three-electrode system was used, with the surface functionalized carbon fiber material as the working electrode, the platinum sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode. The electrodeposition was performed for a period of time at an applied voltage of -0.3 V to obtain a silver nanomaterial-loaded flexible carbon fiber;

[0107] The electrodeposition time described in step 3 is 20 s;

[0108] The mixed solution of AgNO3 and NaNO3 described in step 3 is obtained by dissolving AgNO3 and NaNO3 in water, wherein the concentration of AgNO3 is 100mmol / L and the concentration of NaNO3 is 5mol / L;

[0109] Fourth, compounding the isolation layer with the silver nanomaterial-loaded flexible carbon fiber to obtain a silver nanomaterial-loaded flexible carbon fiber sensor;

[0110] The material of the isolation layer described in step 4 is polyvinyl alcohol;

[0111] The method for compounding the isolation layer and the silver nanomaterial-loaded flexible carbon fiber in step 4 is: using medical tape to adhere the isolation layer and the silver nanomaterial-loaded flexible carbon fiber together.

[0112] The sensors prepared in different embodiments were tested by dropping 20 mL of 50 mM NaCl aqueous solution, and the average potential was determined by measuring three times to verify the repeatability of the response.

[0113] Table 1 Voltage response values ​​of different sensors to 50 mM NaCl

[0114] sensor Voltage (mV) Deviation(mV) Example 1 0.212 0.21 Example 2 0.225 0.24 Example 3 0.244 0.18 Example 4 0.257 0.31 Example 5 0.271 0.28

[0115] It can be seen from Table 1 that the voltage deviation measured by the silver nanomaterial-loaded flexible carbon fiber sensor prepared in Example 3 is the smallest.

[0116] Figure 1 This is a SEM image of the silver nanomaterial-loaded flexible carbon fiber prepared in Example 3 of the present invention;

[0117] from Figure 1 It can be seen that the surface of carbon fiber is loaded with silver nanoparticles.

[0118] Sodium chloride solutions with concentrations of 10, 20, 40, 80, and 100 mM were prepared, and a three-electrode system was used, with the silver nanomaterial-loaded flexible carbon fiber sensor prepared in Example 3 as the working electrode, and the platinum sheet and silver-silver chloride electrode as the counter electrode and working electrode, respectively. Data for 2 minutes were recorded for each concentration of sodium chloride solution as the response voltage value, as shown in FIG. Figure 2 At the same time, the relationship between concentration and voltage is fitted into a corresponding straight line as shown in Figure 3 As shown, the slope of the straight line is 49.76. It can be seen from the figure that the sodium chloride concentration and the voltage present a good linear relationship.

Claims

1. A method for preparing a silver nanomaterial-loaded flexible carbon fiber sensor, characterized in that The preparation method is specifically completed according to the following steps:

1. Pretreatment of carbon fiber: Firstly, the carbon fiber material is cut, then ultrasonically cleaned, and then dried to obtain a pretreated carbon fiber material; 2. In a three-electrode electrolytic cell, the pretreated carbon fiber material is used as the working electrode, the platinum sheet is used as the counter electrode, the Ag / AgCl electrode is used as the reference electrode, and the neutral salt solution is used as the electrolyte. Under the potential window of 0-1 V, the cyclic voltammetry scan rate is selected to perform electrochemical oxidation for a certain number of cycles at room temperature, and then the working electrode is taken out for washing and vacuum drying to obtain a surface functionalized carbon fiber material; 3. At room temperature, the surface functionalized carbon fiber material was immersed in a mixed solution of AgNO3 and NaNO3, and a three-electrode system was used, with the surface functionalized carbon fiber material as the working electrode, the platinum sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode. The electrodeposition was performed for a period of time at an applied voltage of -0.3 V to obtain a silver nanomaterial-loaded flexible carbon fiber; Fourth, compounding the isolation layer and the silver nanomaterial-loaded flexible carbon fiber together to obtain a silver nanomaterial-loaded flexible carbon fiber sensor.

2. The method for preparing a silver nanomaterial-loaded flexible carbon fiber sensor according to claim 1, characterized in that The carbon fiber material described in step one is carbon fiber cloth, carbon fiber felt, carbon fiber sponge or carbon fiber prepreg cloth; in step one, the carbon fiber material is cut into small pieces with a size of (1cm to 3cm)×(1cm to 3cm).

3. The method for preparing a silver nanomaterial-loaded flexible carbon fiber sensor according to claim 1, characterized in that The ultrasonic cleaning process described in step 1 is: ultrasonic cleaning is performed using acetone, anhydrous ethanol and deionized water in sequence for 10 minutes to 60 minutes respectively; the drying temperature described in step 1 is 60° C. to 90° C.

4. The method for preparing a silver nanomaterial-loaded flexible carbon fiber sensor according to claim 1, characterized in that The neutral salt solution described in step 2 is sodium sulfate solution, potassium sulfate solution, zinc sulfate solution or iron sulfate solution.

5. The method for preparing a silver nanomaterial-loaded flexible carbon fiber sensor according to claim 1, characterized in that The concentration of the neutral salt solution described in step 2 is 1 mol / L to 3 mol / L.

6. The method for preparing a silver nanomaterial-loaded flexible carbon fiber sensor according to claim 1, characterized in that The number of cycles of electrochemical oxidation in step 2 is 10 to 30 cycles; the scanning rate of cyclic voltammetry in step 2 is 1 mVs -1 ~10mVs -1 .

7. The method for preparing a silver nanomaterial-loaded flexible carbon fiber sensor according to claim 1, characterized in that In step 2, the working electrode is taken out and washed with deionized water for 3 to 5 times; the vacuum drying temperature in step 2 is 60° C.; and the electrodeposition time in step 3 is 10 s to 90 s.

8. The method for preparing a silver nanomaterial-loaded flexible carbon fiber sensor according to claim 1, characterized in that The mixed solution of AgNO3 and NaNO3 described in step 3 is obtained by dissolving AgNO3 and NaNO3 in water, wherein the concentration of AgNO3 is 10mmol / L to 50mmol / L, and the concentration of NaNO3 is 1mol / L to 10mol / L.

9. The method for preparing a silver nanomaterial-loaded flexible carbon fiber sensor according to claim 1, characterized in that The material of the isolation layer described in step four is polyvinyl alcohol; the method of compounding the isolation layer and the silver nanomaterial-loaded flexible carbon fiber in step four is: using medical tape to adhere the isolation layer and the silver nanomaterial-loaded flexible carbon fiber together or sewing the isolation layer and the silver nanomaterial-loaded flexible carbon fiber together.

10. Application of a silver nanomaterial-loaded flexible carbon fiber sensor prepared by the preparation method according to claim 1, characterized in that A silver nanomaterial-loaded flexible carbon fiber sensor for sweat detection.